The Influence of Influencer Marketing and Consumer Trust on the Repurchase Intention of Local Fashion Products in Medan Helvetia District: Pengaruh Influencer Marketing dan Kepercayaan Konsumen terhadap Repurchase Intention Produk Fashion Lokal di Kecamatan Medan Helvetia - Jennifer Leslie; Pesta Gultom; Marlo Novino; Shiny Rose Narit (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to analyze the influence of influencer marketing and consumer trust simultaneously or partially on the repurchase intention of local fashion products in Medan Helvetia District. The method used was descriptive quantitative with a questionnaire survey distributed to 100 consumer respondents aged 18-35 years in the research area. The collected data was analyzed using SPSS software through instrument validity and reliability tests, normality, multicollinearity, and multiple linear regression. The results of the analysis showed that influencer marketing had a positive and significant effect on repurchase intention with a regression coefficient of 0.427 (t = 4.844, p < 0.05), as well as consumer confidence which made a significant positive contribution with a coefficient of 0.466 (t = 4.817, p < 0.05). Simultaneously, the two variables were able to explain 60.8% variation in repurchase intent (F = 75,145, p < 0.05), while the rest were influenced by other factors outside of this study. These findings provide empirical evidence for local fashion businesses to prioritize long-term collaboration strategies with influencers as well as efforts to strengthen consumer trust to increase loyalty and sustainable sales growth.